Association Between the New Hampshire Parental Notification Law and Minors Undergoing Abortions in Northern New England. Issue 1 (January 2015) - MacAfee, Lauren; Castle, Jennifer; Theiler, Regan N.
Abstract : OBJECTIVE: To assess the association of the 2012 New Hampshire parental notification law with patterns of abortion in northern New England minors. METHODS: This was a retrospective cohort study examining all minors undergoing abortions at Planned Parenthood clinics in Vermont, New Hampshire, and Maine from 2011 to 2012. RESULTS: The number of abortions among minors in New Hampshire decreased from 95 to 50 (47%, 95% confidence interval [CI] 37.03–57.88; P =.015) from 2011 to 2012. Minors residing in Massachusetts, which has a parental consent law, accounted for 62% of this change. Abortions among New Hampshire minors decreased by 19% (from 57 to 46, 95% CI 10.05–31.91; P =.707), and minors did not seek more abortions at Planned Parenthood clinics in Vermont or Maine. The average age, gestational age, and number of second-trimester cases did not change. Parental awareness of the abortion increased from 2011 to 2012 in New Hampshire (54%, 95% CI 44.21–63.96 to 92%, 95% CI 80.65–97.36; P <.001); however, there was no difference in the overall rate of adult involvement during the study period. Four (8%) minors in New Hampshire used the judicial bypass option. CONCLUSION: Implementation of the New Hampshire parental notification law correlated with a decrease in minors undergoing abortions at Planned Parenthood clinics in the state, largely as a result of a decrease in the number of minors coming from Massachusetts. There was an increase in parental involvement but no change in overall adult involvement, and use of the judicial bypass option or minors crossing state lines was uncommon. Abstract : The New Hampshire parental notification law results in more parental involvement and fewer abortions among minors in the state and is associated with a decrease in Massachusetts minors traveling to New Hampshire.